The Influence of Media on Hijab wearing in Malaysia: A Study among Malays (Pengaruh Media Terhadap Pemakaian Hijab di Malaysia: Satu Kajian di Kalangan Orang Melayu) - A. Manaf, Aini Maznina; Wok, Saodah (Journal of Islam in Asia (E-ISSN 2289-8077), 2019)
Hijab wearing among Muslim women is currently seen as a common phenomenon in Malaysia. Is the religious awareness among them on the rise? Or is it just fashion or a trend? Many studies have been conducted to understand factors that influence hijab wearing among Muslim women. Nonetheless, little information is available on the roles that the media play in influencing women’s decision to wear hijab. This study is conducted to find out the perception of Muslim women on the extent to which media and people surrounding them influence their hijab (head cover) wearing. Specifically, the objectives of this study are (1) to find out the patterns of hijab wearing, (2) to find out sources of media influence on hijab wearing among Malay women, (3) to determine sources of social/interpersonal influence on hijab wearing among Malay women, (4) to compare between the media influence and the social/interpersonal influence on hijab wearing among Malaysian women, and (5) to analyze the extent of media and social/interpersonal influence that impact change on hijab wearing. Using data from a survey conducted on 362 female students from an Islamic Higher Education Institution in Malaysia, the findings reveal that Facebook, blog and magazine are the top three highest media influencing impact change on hijab wearing. Parents, friends/colleagues and siblings have more influence on hijab wearing than the other sources. Social/interpersonal influence has a bigger impact than the media in influencing hijab wearing. In addition, both the media influence and the social/interpersonal influence are positively related to one another. The Malay women admit that hijab wearing has much/very much changed them towards being good Muslims. Keywords: hijab wearing, Malay women, media influence, social/interpersonal influence, impact change. Abstrak Pemakaian hijab di kalangan wanita Islam dilihat sebagai satu fenomena yang biasa di Malaysia. Adakah ia menunjukkan kesedaran agama di kalangan mereka semakin meningkat? Atau ia hanya sekadar fesyen atau gaya hidup? Banyak kajian telah dijalankan untuk melihat faktor-faktor yang mempengaruhi pemakaian hijab di kalangan wanita Islam. Walau bagaimana pun, hanya sedikit maklumat berkenaan peranan media dalam mempengaruhi pemakaian hijab di kalamgan wanita Islam. Secara khusus, objektif kajian ini (1) untuk mengetahui bentuk pemakaian hijab, (2) untuk mengetahui sumber pengaruh media terhadap pemakaian hijab di kalangan wanita Melayu, (3) untuk mengetahui sumber pengaruh sosial/interpersonal terhadap pemakaian hijab di kalangan wanita, (4) untuk membuat perbandingan antara pengaruh media dan sosial/interpersonal terhadap pemakaian hijab, dan (5) untuk menganalisa tahap pengaruh media dan sosial/interpersonal ke atas kesan perubahan daripada pemakaian hijab. Satu kaji selidik dijalankan di kalangan 362 pelajar wanita dari sebuah insititusi pengajian tinggi di Malaysia, dapatan menunjukkan facebook, blog dan majalah merupakan tiga media yang tertinggi dalam mempengaruhi kesan perubahan ke atas pemakaian hijab di kalangan responden. Ibubapa, rakan/rakaan sekerja serta adik beradik pula mempunyai pengaruh yang lebih tinggi dari sumber lain. Pengaruh sosial/interpersonal pula adalah lebih tinggi daripada media dalam mempengaruhi pemakaian. Selain daripada itu, kedua-dua pengaruh iaitu media dan sosial/interpersonal adalah berkait rapat secara positif di antara satu sama lain. Wanita Melayu mengakui bahawa pemakaian hijab banyak mempengaruhi mereka untuk menjadi penganut Islam yang baik. Kata Kunci: pemakaian hijab, wanita Islam, pengaruh media, pengaruh sosial/interpersonal, kesan perubahan.